Daratumumab eradicates minimal residual disease in a preclinical model of pediatric T-cell acute lymphoblastic leukemia - Vogiatzi, Fotini; Winterberg, Dorothee; Lenk, Lennart; Buchmann, Swantje; Cario, Gunnar; Schrappe, Martin; Peipp, Matthias; Richter-Pechańska, Paulina; Kulozik, Andreas; Lentes, Jana; Bergmann, Anke K.; Valerius, Thomas; et al. (Blood, 2019)
TO THE EDITOR:Novel immunotherapies have recently led to a broadened spectrum of therapeutic options in pediatric B-cell precursor acute lymphoblastic leukemia, even in the setting of relapsed/refractory disease. However, antibody therapy for T-cell acute lymphoblastic leukemia (T-ALL) is currently nonexistent, and no antibody has been approved for clinical use in that entity. Bride et al have recently reported in Blood that the CD38-targeting antibody daratumumab (DARA), approved for the treatment of multiple myeloma, has preclinical efficacy in T-ALL patient-derived xenografts (PDXs) in nonobese diabetic/severe combined immunodeficiency/Il2rgtm1wjl/SzJ (NSG) mice.1 Off-label use has been reported in 1 adult T-ALL patient with post-stem cell transplantation relapse in whom the relapse could be salvaged with DARA.2 Here, we asked whether the addition of DARA could enhance the efficacy of chemotherapy mimicking ALL induction in a preclinical PDX model of T-ALL. Furthermore, we aimed to assess depth of remission achievable with DARA and whether CD38 expression levels were correlated with therapy response.
Gesehen am 08.12.2020